Role of GTPase-Dependent Mitochondrial Dynamins in Heart Diseases - Liu, Jiangen; Song, Xianjing; Yan, Youyou; Liu, Bin (Frontiers in Cardiovascular Medicine, 2021)
The maintenance of heart function requires a large amount of energy, which is supplied by mitochondria. In addition to providing energy to cardiomyocytes, mitochondria also play an important role in maintaining cell function and homeostasis. Although adult cardiomyocyte mitochondria appear as independent, low-static organelles, morphological changes in cardiomyocyte mitochondria have been observed under stress or pathological conditions. Therefore, cardiac mitochondrial fission and fusion are involved in the occurrence and development of heart diseases, as confirmed by many studies. As mitochondrial fission and fusion are mainly regulated by mitochondrial dynamins in a GTPase-dependent manner, GTPase-dependent mitochondrial fusion (MFN1, MFN2, and OPA1) and fission (DRP1) proteins, which are very abundant in the adult heart, can also be regulated in heart diseases. Dynamic proteins such as these, have been found to play very important roles in diseases such as ischemia-reperfusion injury, heart failure, and metabolic cardiomyopathy. This article reviews the role of GTPase-dependent mitochondrial fusion and fission protein-mediated mitochondrial dynamics in the occurrence and development of heart diseases.